PENERAPAN KURIKULUM MERDEKA TERHADAP GAYA BELAJAR SISWA DI MI/SD - Doni Angyanur; Nurhidayati; Siti Lutfiah Azzahra; Anjani Putri Belawati Pandiangan (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2022)
In this study, the authors conduct research based on a collection of several articles, books and journals that discussed changes in the independent curriculum on students' learning styles in MI/SD. In the independent curriculum there were 4 very important changes, namely; curriculum structure is more flexible, focuses on essential material, uses several teaching tools, and utilizes digital technology. From these changes it is certain that this is a process of adjusting the education process to the changing times where currently the technology and digital era has very much taken over the world. Of course this must be related to adjustments to students' learning styles at school, because the period in elementary school is the golden age for children to be able to determine the direction in which they are going in the process of finding their own identity.